Women’s Experiences of Immigration Detention in Italy: Examining Immigration Procedural Fairness, Human Dignity, and Health - Esposito, Francesca; Di Martino, Salvatore; Briozzo, Erica; Arcidiacono, Caterina; Ornelas, Jose (Frontiers in Psychology, 2022)
In recent years, an increasing number of states around the world, particularly in the so-called Global North, have been using border control measures, including immigration detention, to govern human mobility and confine those classified as unauthorised non-citizens. In response to this, an increasing number of scholars from different disciplines, including psychology, have put their efforts into studying this phenomenon. This study is the first of its kind to have surveyed 100 people confined in Rome’s detention centre, the largest Italian immigration detention facility. Results from a latent Path Analysis within the framework of Structural Equation Modelling revealed the potential mediating role of the lack of human dignity between immigration procedural justice and the physical and mental health perceived by the people confined, even after controlling for pre-existing physical and mental health conditions. Our study is an attempt to sheds light on the dehumanisation and damage to human dignity that immigration detention entails, as well as its negative impact on the health of those directly affected. This evidence reinforces the image of detention centres as sites of persistent injustice, while stressing the need for psychologists to take a stand and channel their efforts to envision justice-oriented forms to address human mobility.